2013
DOI: 10.5578/mb.4543
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Coxiella burnetii Prevalence in Women Who Had Miscarriage and Their Spouses by Serological and Molecular Methods

Abstract: ÖZETCoxiella burnetii yaygın bir zoonoz olan Q ateşinin etkenidir. İnsanlara, sıklıkla çiftlik hayvanlarının süt, idrar ve özellikle enfekte doğum atıklarından kaynaklanan kontamine aerosollerin inhalasyonuyla bulaşır. Etkenin cinsel yolla da bulaştığı bildirilmektedir. Gebelerde özellikle birinci trimesterde, akut Q ateşinin abortusa neden olduğu, gebeliğin ilerleyen dönemlerinde hastalığın kronikleşme eğilimi gösterdiği ve düşük doğum ağırlığı ve prematüre doğumlara sebep olduğu gösterilmiştir. Bu çalışmada,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the prevalence of C. burnetii in abortion samples from pregnant women using molecular methods. One study conducted in Turkey on 51 placental samples found no detection of C. burnetii [ 35 ]. Similarly, a study in France on 246 placenta samples also reported no infection with this pathogen [ 36 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the prevalence of C. burnetii in abortion samples from pregnant women using molecular methods. One study conducted in Turkey on 51 placental samples found no detection of C. burnetii [ 35 ]. Similarly, a study in France on 246 placenta samples also reported no infection with this pathogen [ 36 ], which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the prevalence of Q fever in pregnant women using serological methods. In two separate studies conducted in Turkey, the seroprevalence of Q fever among pregnant women was found to be 20.7% and 14%, respectively [ 35 , 39 ]. In Iran, the seroprevalence of C. burnetii infection in pregnant women was found to be 22% in the southwest (Ahvaz City) and 36.5% in the north (Parsabad City).…”
Section: Discussionmentioning
confidence: 99%